Lignin-carbohydrate complexes from sugarcane bagasse: preparation, purification, and characterization - Singh, R.; Singh, S.; Trimukhe, K. D.; Pandare, K. V.; Bastawade, Kulbhushan B.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2005)
Lignin-carbohydrate complexes were isolated from sugarcane bagasse by a process, which yielded sulfur-free lignins. These could be made carbohydrate-free, if necessary, by treatment with xylanase enzyme. A study of the preparation, purification, and characterization of such lignin-carbohydrate complexes, comparison with commercial lignin samples (wood based as well as bagasse based) and some other lignin derivatives was made by using a variety of analytical tools such as FTIR, HPLC at three different UV-wavelengths, GPC, thermal analysis and elemental analysis. The use of such a diverse range of lignin-carbohydrate complex samples enabled us to predict the sensitivity of the various analytical techniques for characterization of complex polymers containing carbohydrate moieties. Evidence for lignin-carbohydrate complex was detectable by FTIR as well as HPLC studies. Thermal analysis studies showed the crucial effect of carbohydrate groups, the content of aliphatic chains, and the sulfur content of the lignins. Generalized structures of lignin-carbohydrate complexes obtained from various sources using different preparation methods and chemical modifications are presented. This will aid the applications development effort with advantageously using lignins containing low levels of carbohydrate moieties as reactive sites as well as biodegradability inducing sites. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: biodegradability; hardwood lignins; lignin-carbohydrate complex; softwood lignins; Sugarcane bagasse; sulfur-free lignins; xylanase enzyme

Carbon quantum dots functionalized agarose gel matrix for in solution detection of nonylphenol - Singh, S.; Nigam, P.; Pednekar, A.; Mukherjee, S.; Mishra, A. (Environmental Technology, 2020)
Nonylphenol, an endocrine disrupter, is widely released to the aquatic environment, which is accumulative and extremely toxic to aquatic organisms. Here, we report a simple and cost-effective large-scale green synthesis of water-soluble highly fluorescent carbon quantum dots (CQDs) from marine biowaste (offshore washed algae) which gets quenched strongly in the presence of nonylphenol. These CQDs were around 20-40 nm in size and exhibit fluorescence constantly at 360 nm. The XRD profile depicted the interlayer spacing in the particle as 0.284 nm with a humped peak around 14 degrees showing the amorphous nature of the CQDs. FTIR spectra showed the stretching vibration of the hydroxyl groups (OH), asymmetric and symmetric stretching vibrations of the carboxylate anions (COO-). The fluorescence quantum yield of the CQDs is up to 68% and nonyl phenol detection limit is less than 0.1 µM. Furthermore, the CQDs were found to be stable at a wide pH range which makes it a suitable nonylphenol sensor for a variety of environmental samples. We functionalized these CQDs on an agarose gel matrix to develop a convenient sensor for the rapid detection of nonylphenol.
Keywords: Carbon quantum dots; endocrine disrupter; marine algae; nonylphenol; pollutant